Avaliação da atividade biológica de β- Citronelol sobre Candida albicans - Silva, Daniele de Figueredo (2016)
Candida albicans is the main yeast provider of opportunistic fungal infections in healthy humans and immunossupressed. The high frequency candidiasis, linked to increased therapeutic failure by reflection of resistance to antifungal agents commonly used therapy leads to search for alternative sources for obtaining new antifungal drugs. Highlighted, natural herbal products are excellent precursors for diversity of active molecular compounds. Among them, the monoterpenes are holders of a huge biological potential of human interest. Given these premises, we evaluated the biological activity of β - citronellol on Candida albicans, by microbiological tests performed in vitro by determining the minimum inhibitory concentration (MIC), followed by the Fungicide Concentration Minimum (CFM) and disk diffusion testing solid medium, for comparative study of the susceptibility profile to azole antifungals (ketoconazole, clotrimazole, fluconazole, itraconazole and miconazole) and polyenes (amphotericin B and nystatin) isolated or as association with β -.citronellol. In addition, studies were also made of ADMET parameters by in silico analysis. In studies of antifungal activity, β - citronellol obtained a MIC of 128 mg / mL (strong activity) and CFM 512 ug / mL respectively for 75% of the population of the tested fungal strains. The association study, synergism was prevalent for all antifungals. In highlighted, the combination of β- citronellol to fluconazol, itraconazole, miconazole, were found to change the sensitivity of the resistance profile for some specimens of C. albicans. In the in silico analysis, β - citronellol showed good oral bioavailability, however, irritation potential and damage to the reproductive system have been disclosed as possible severe toxicological effects to this monoterpene. In conclusion, the β- citronellol monoterpene has to have anti-Candida albicans activity of fungicide nature, besides being a great modifier of the antifungal activity when combined. And although it presented good theoretical oral bioavailability, varied toxicological profile suggests the need to assess the risk-benefit of this compound in the production of new antifungal medicine for conducting preclinical and clinical trials of nature.